GRATITUDE SEBAGAI MEDIATOR ANTARA MINDFULNESS DAN PENERIMAAN DIRI - Ikkyu Ikkyu; Livia Yuliawati (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2022)
Social media nowadays has become a need of many people. One of the most used social media is Instagram.Ease of access to look into the lives of others and evaluate others contributes to the decreasing ability toaccept oneself. This study aims to examine the role of gratitude as the mediator between mindfulness and self-acceptance among Instagram users. The present study involves 121 participants, age from 18 to 24 years oldusing convenience sampling method. Gratitude Questionnaire Six Item Form (GC-6), Mindful AttentionAwareness Scale (MAAS), and Berger’s Self-Acceptance Scale are administered using online survey. Results havefound that gratitude significantly acts as the significant partial mediator between mindfulness and self-acceptance. Mindfulness and gratitude play important roles for active Instagram users to be able to acceptthemselves for what they are.